Chromium-containing silica materials - Godoi, R. H M [UNESP]; Jafelicci, M. [UNESP]; Davolos, Marian Rosaly [UNESP]; Fernandes, L. [UNESP]; Martines, M. A U [UNESP]; Portillo, J. (Elsevier, 2000)
Chromium-containing silica samples were obtained from soluble sodium silicate solutions in the presence of different chromium nitrate concentrations. Precipitation was carried out in ethanolic media. Gel precipitate was dried by liophylization and samples measured by transmission electron microscopy (TEM), X-ray energy-dispersive spectrometer, X-ray mapping, X-ray photoemission spectroscopy (XPS), and particle size analysis. Spherical chromium containing silica particles with 3.5% and 4.8% (at.%) of chromium were obtained. Particle size analysis results showed that with increased addition of chromium in sodium silicate solutions produces agglomerates whose sizes range from 1 to 0.2 μm. Chromium mapping and XPS results show that chromium oxide is preferentially segregated on particle surfaces. Chromium oxide was detected on particle surface with a binding energy of 576.77 ± 0.05 eV as obtained from XPS analysis. During the hydrolysis and condensation processes chromium oxide precipitates on the silica surface and it affects the silica chain size. © 2000 Elsevier Science B.V. All rights reserved.